Outpatient Care of the Interventional Radiology Patient - Siskin, Gary (Thieme Medical Publishers, 2006)
The current trend among interventional radiologists is to be actively involved in the pre- and post-procedure care that surrounds many of our procedures. For this to occur, defined office space that is set up in such a way that is conducive to outpatient consultation and post-procedure visits is required. In addition, appropriate support staff such as midlevel providers (including nurse practitioners and physician assistants) and a receptionist are needed to make the entire system work. Finally, dedicated time to focus on direct patient care is mandatory. Equally important is understanding the processes that occur in the background of a typical procedural encounter, including generating referrals, obtaining insurance pre-authorization, managing medical records, and communicating with referring physicians, all of which are expected to take place when managing patients in an outpatient setting. When these components are in place, it becomes possible for an interventionalist to successfully develop an outpatient office and to meet the expectation that patients will be seen before and after procedures by the practitioner performing that procedure.